Landing techniques in beach volleyball - Tilp , M.; Rindler, M. (Journal of Sports Science & Medicine, 2013)
The aims of the present study were to establish a detailed and representative record of landing techniques (two-, left-, and right-footed landings) in professional beach volleyball and compare the data with those of indoor volleyball. Beach volleyball data was retrieved from videos taken at FIVB World Tour tournaments. Landing techniques were compared in the different beach and indoor volleyball skills serve, set, attack, and block with regard to sex, playing technique, and court position. Significant differences were observed between men and women in landings following block actions (X²(2) = 18.19, p < 0.01) but not following serve, set, and attack actions. Following blocking, men landed more often on one foot than women. Further differences in landings following serve and attack with regard to playing technique and position were mainly observed in men. The comparison with landing techniques in indoor volleyball revealed overall differences both in men (X²(2) = 161.4, p < 0.01) and women (X²(2) = 84.91, p < 0.01). Beach volleyball players land more often on both feet than indoor volleyball players. Besides the softer surface in beach volleyball, and therefore resulting lower loads, these results might be another reason for fewer injuries and overuse conditions compared to indoor volleyball.